2020
DOI: 10.1021/acsami.0c16563
|View full text |Cite
|
Sign up to set email alerts
|

New Strategies for Engineering Tensile Strained Si Layers for Novel n-Type MOSFET

Abstract: We report a novel approach for engineering tensely strained Si layers on a relaxed Silicon Germanium On Insulator (SGOI) film using a combination of condensation, annealing and epitaxy in selected conditions well chosen based on elastic simulations. The study evidences the remarkable role of SiO2 buried oxide layer (BOX) on the elastic behavior of the system. We show that tensely strained Si can be engineered by using alternatively rigidity (at low temperature) and viscoelasticity (at high temperature) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…[ 58–62 ] Similar results can be obtained by deposition of stressors [ 63 ] or by deposition of Si atop a strained substrate (e.g. made of SiGe) [ 64 ] opening the way to finely control the position of the ZPL of the emitters (e.g. with respect to a photonic resonance of a resonant cavity).…”
Section: Discussionmentioning
confidence: 76%
“…[ 58–62 ] Similar results can be obtained by deposition of stressors [ 63 ] or by deposition of Si atop a strained substrate (e.g. made of SiGe) [ 64 ] opening the way to finely control the position of the ZPL of the emitters (e.g. with respect to a photonic resonance of a resonant cavity).…”
Section: Discussionmentioning
confidence: 76%
“…They report a significant compressive strain of about 1% at 900°C while at 1000°C, this compressive strain is reduced to 0.7% due to the intermixing between the Si with the Si 1-x Ge x layer and the Si 1-x Ge x layer is completely relaxed at 1080 °C. A recently developed process based on condensation/annealing steps has created tensilely strained Si layers epitaxially grown on relaxed SGOI with −0.85% tensile strain in the out-of-plane direction for multifinger 2.5 V n-type MOSFET on SOI for RF-switch applications [38]. In parallel, it was reported that during high temperature treatment, the SiO 2 film becomes viscous and the strained thin film on this viscous oxide is morphologically unstable.…”
Section: Introductionmentioning
confidence: 99%